Assessment of Management Factors Influencing Vaccination Against Cholera in the Health District of Katana, the Democratic Republic of the Congo. - Ntererwa-Nsimire, Irène; Irenge, Leonid M; Mutombo, Paulin B; Mafuta, Eric M; Gala, Jean-Luc; Ngo-Bebe, Dosithée (Health Services Insights, 2025)
Cholera remains a major healthcare issue in the Democratic Republic of the Congo with recurrent cholera outbreaks in its eastern provinces since 1994. Cholera cases and deaths increased from 18 403 and 302 in 2022 to 52 570 and 470 in 2023. From October 1st to December 31st, 2022, we conducted a mixed descriptive study to analyze the management process underpinning the cholera vaccination campaign in the Katana health district, South Kivu province, DRC. The survey targeted households (n = 404) with 1 adult person per household responding on behalf of all the members of the household and key informants (KI) who were health workers (n = 6) in 5 health areas of the Katana health district. The overall cholera prevalence in the surveyed households was 4.7% (95% CI 2.9-7.3), and the overall vaccination rate was 25.0% (95% CI 20.9-29.5). Most interviewed household respondents (54.5%) were eager for their household members to get vaccinated, and 61% had to walk for more than 1 hour to reach the vaccination center. Cholera vaccine for children under 2 years was available in all the 5 health areas investigated, only 2 out of 5 health areas had enough vaccine stockpiles. Only 33.3% of KI administering vaccines were trained at least once during the past 3 years. All the KI (100%) complained about delays or absence of payment for their services which negatively impacted their implication. Our findings highlight weaknesses in the planning of the last cholera vaccination campaign in the health district of Katana.